Industrial Demand Response : Methods, Best Practices, Case Studies, and Applications. - Alhelou, Hassan Haes (Energy Engineering Ser., 2022)
Demand response (DR) describes controlled changes in the power consumption whose role is to better match the power demand with the supply. This reference, written by an international team of experts from academia and industry, covers the principles, implementation and applications of DR.